The first West Indies cricket tour : Canada and the United States in 1886 - Beckles, Hilary McD. (Canoe P. KingstonJM, 2006)
Provides an introduction to the historic West Indian Tour. Gives the background to the Tour and looks at cricket in the United States in 1886. Deals with the West Indian team in Canada and the United States\n